Multinational corporations and commercialised states: Can state aid serve as the basis for an FDI-driven growth strategy? - Ryan Woodgate (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
In recent decades, governments around the world have increasingly used various forms of state aid to try to attract and retain the business activity of foreign-owned multinational corporations. Yet, in most cases, this "commercialisation of state sovereignty" (Palan, 2002) has failed to catalyse foreign investment and economic growth as intended. This paper seeks to understand the general failure of such commercialised state strategies, while also explaining how demand and income growth in some notable exceptions can be understood. To this end, a simple demand-led model is presented that suggests that foreign-targeted state aid may lead to beggarthy-neighbour, FDI-driven growth in one economy if certain conditions are met, such as there being sufficiently little policy competition from other countries. It is shown that the exceptional cases tend to be the early movers, i.e. those few economies and special economic zones that engaged in the commercialisation of state sovereignty before the widespread competitive emulation that followed. This paper argues that state aid for the attraction of foreign multinationals is unlikely to be an effective growth strategy in the current environment of intense state competition and that international coordination on corporation tax and other forms of state aid is desirable.
Keywords: E12; F23; F62; H26; H71; 330; policy competition; foreign direct investment; tax havens; export platforms